A graphene van der waals contact electrode based on a sacrificial copper catalytic layer and a preparation method thereof
Patent Information
- Application Number
- CN202611306529.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-27
AI Technical Summary
然而,在金属沉积过程中,高能金属原子容易对二维半导体材料表面造成损伤,并在接触界面处引入缺陷态及污染物,同时,金属与MoS2等二维材料接触时容易出现费米能级钉扎现象,影响器件的电学性能与稳定性
1、本发明首先提供了一种范德华接触电极,该接触电极的待测二维材料区无需直接经历金属沉积或与金属接触,可有效减少界面损伤、缺陷和污染,该结构可提高器件的制备一致性、稳定性。
Smart Images

Figure CN122995228A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of two-dimensional material electronic device fabrication technology, specifically relating to a graphene van der Waals contact electrode based on a sacrificial copper catalyst layer and its preparation method. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Two-dimensional materials (such as monolayer MoS2 and graphene) have been widely used in electronic and optoelectronic devices such as field-effect transistors and Hall effect sensors in recent years due to their atomic-level thickness and excellent electrical and optical properties. These devices typically rely on metal-semiconductor contacts for carrier injection and signal transmission; therefore, the quality of the contact interface directly affects the electrical performance and stability of the device. Currently, a common method for constructing metal-two-dimensional semiconductor contacts is to directly deposit metal electrodes on the surface of the two-dimensional material. This approach usually involves first preparing or transferring two-dimensional semiconductor materials such as MoS2 onto the surface of a SiO2 / Si substrate, then defining the source and drain electrode patterns using photolithography, and subsequently depositing metal electrodes such as Ti / Au, Cr / Au, and Ni / Au directly on the surface of the two-dimensional semiconductor material using methods such as thermal evaporation, electron beam evaporation, or magnetron sputtering, finally forming a direct metal-two-dimensional semiconductor contact structure. The difference between this scheme and the present application is that the prior art involves direct contact between the metal and the two-dimensional material, while in the present application, the Cu layer is only used to grow graphene and is subsequently removed by thermal evaporation; before the transfer of the two-dimensional material, the graphene contact electrode and the Cr / Au lead-out end have been pre-prepared, and the transferred two-dimensional material only contacts the graphene and does not directly contact the Cr / Au.
[0004] Existing technologies often damage the surface of two-dimensional materials during direct metal deposition, and may introduce defect states and contaminants at the contact interface. Furthermore, Fermi level pinning is common when metals contact two-dimensional semiconductors such as MoS2, making it difficult to effectively control the Schottky barrier, resulting in high contact resistance and low carrier injection efficiency. Therefore, there is a need for a two-dimensional semiconductor contact structure and its fabrication method that can reduce interface damage, avoid direct metal contact with the two-dimensional material channel region, lower contact resistance, and improve device uniformity. Summary of the Invention
[0005] Existing two-dimensional semiconductor devices typically construct source / drain contacts by directly depositing metal electrodes on the surface of the two-dimensional semiconductor material. However, during metal deposition, high-energy metal atoms can easily damage the surface of the two-dimensional semiconductor material and introduce defect states and contaminants at the contact interface. Furthermore, Fermi level pinning can easily occur when the metal contacts two-dimensional materials such as MoS2, affecting the electrical performance and stability of the device. To address these issues, this application provides a graphene van der Waals contact electrode based on a sacrificial copper catalyst layer and its fabrication method. The graphene contact electrode is fabricated using a sacrificial Cu catalyst layer, and a Cr / Au metal lead is deposited at the distal end to overlap with the graphene. This ensures that only graphene serves as the van der Waals contact electrode in the two-dimensional material contact area, thereby avoiding direct metal contact with the two-dimensional material channel region, reducing interface contamination and defects, improving device contact performance, and enhancing fabrication consistency.
[0006] Based on the aforementioned technical effects, the present invention provides the following technical content: In a first aspect, a method for fabricating a graphene van der Waals contact electrode based on a sacrificial copper catalyst layer is provided, wherein the contact electrode uses a SiO2 / Si substrate or a SiO2 / SiC as the device substrate, wherein Si or conductive SiC is used as a global back gate. The contact electrode has three regions on its SiO2 layer: the two-dimensional material to be tested region, the graphene electrode, and the large metal electrode, which are sequentially overlapped. The two-dimensional material to be tested region is used to place the material to be tested and is in contact with the graphene electrode. The large metal electrode partially covers the graphene layer electrode, and the two-dimensional material to be tested and the large metal electrode are not in direct contact. The metal large electrode comprises at least one metal element.
[0007] In the contact electrode described in the first aspect above, the two-dimensional material region under test only contacts the graphene electrode and not the large metal electrode. The distal large metal electrode serves as a lead-out terminal, overlapping with the graphene electrode for connecting to external test circuits. This arrangement effectively reduces interface contamination and defects caused by direct metal deposition. Secondly, the separation of the large metal electrode from the two-dimensional material region under test avoids Fermi level pinning, effectively improving the electrical performance and stability of the contact electrode.
[0008] Furthermore, the aforementioned device first constructs a Cu layer in the graphene electrode region using methods such as magnetron sputtering or evaporation deposition. The Cu layer serves solely as a catalyst layer for graphene growth. After graphene is formed on the surface of the Cu layer, the Cu layer is removed by thermal evaporation, ensuring that only graphene remains in the predetermined graphene electrode region as the graphene electrode.
[0009] Furthermore, in some embodiments verified by the present invention, the contact electrode of the first aspect described above also has the following preferred embodiment: In the aforementioned device substrate, the SiO2 layer has a thickness of 100-300 nm; furthermore, the Si substrate or SiC substrate serving as the global back gate should be of a conductive doped type, wherein the Si substrate is heavily doped single-crystal silicon, and may be p-type. + Type boron-doped silicon or n + Phosphorus / arsenic / antimony doped silicon; silicon crystal orientation can be (100) or (111), crystal growth method can be Czochralski silicon or zone-grown silicon; the SiC substrate is a heavily doped conductive silicon carbide single crystal, crystal polymorph can be 4H-SiC or 6H-SiC, and conductivity type can be n-type nitrogen doped SiC or p-type aluminum doped SiC.
[0010] Furthermore, the thickness of the graphene layer is 0.34-1 nm.
[0011] Furthermore, the two-dimensional material region to be tested is covered with graphene material or MoS2 with a thickness of 0.34-1 nm, and the two-dimensional material to be tested is placed on it.
[0012] Furthermore, in one embodiment verified by the present invention, the above-mentioned large metal electrode includes a Cr layer and an Au layer, wherein the Cr layer is close to the SiO2 surface and has a thickness of 3-10 nm, and the Au layer completely covers the Cr layer and has a thickness of 30-100 nm.
[0013] Secondly, a method for preparing the graphene van der Waals contact electrode based on the sacrificial copper catalyst layer described in the first aspect is provided, comprising the following steps: S1. Substrate cleaning and photolithography patterning SiO2 / Si or SiO2 / SiC substrates are selected as the device substrate, and Si or conductive SiC is used as the global back gate. The substrates are cleaned and dried. A pre-defined graphene electrode region pattern is formed on the SiO2 surface by photolithography to obtain the pre-defined pattern substrate. Deposition and stripping of S2.Cu sacrificial catalyst layer On the surface of the pre-patterned substrate obtained in S1, a Cu sacrificial catalyst layer is formed by magnetron sputtering or evaporation deposition to obtain the Cu sacrificial catalyst layer. S3. Graphene growth and thermal evaporation removal of Cu layer The Cu sacrificial catalyst electrode obtained in S2 is placed in a chemical vapor deposition apparatus. A carbon source gas is introduced to grow a single or few-layer graphene film on the surface of the Cu sacrificial catalyst. After the carbon source is stopped, annealing is performed in a reducing gas atmosphere to remove the Cu sacrificial catalyst by thermal evaporation or volatilization, leaving only the graphene layer, which is referred to as the graphene layer contact electrode. S4. Deposition and stripping of large metal electrodes A second photolithography is performed on the graphene electrode to form a secondary preset pattern region for the metal large electrode. Metal is deposited in the secondary preset pattern region to form the metal large electrode, which does not overlap with the graphene layer mentioned above, but only partially overlaps with it. S5. Transfer and annealing of the two-dimensional material to be tested Two-dimensional material is partially covered on the surface of a graphene film to form the two-dimensional material region to be tested, which is then in contact with the graphene electrode; annealing improves the contact performance, thus obtaining the complete device.
[0014] The preparation method described in the second aspect above also has the following preferred embodiments: In S1, the purpose of the cleaning is to fully remove residual impurities on the substrate surface. Feasible methods include cleaning with organic reagents and water or using RCA standard wet cleaning. In one embodiment verified by the present invention, feasible organic reagents such as acetone and isopropanol are used to ultrasonically clean the substrate in sequence with acetone, deionized water and isopropanol, with each reagent cleaning time being 5 to 15 minutes.
[0015] The photolithography methods described in S1 and S4 above are as follows: Photoresist is spin-coated onto the substrate surface, and a preset electrode pattern is formed through exposure and development processes. Feasible photoresist models include one of AZ5218E, AZ5206E, AZ5200NJ, AZnLoF5510, and AZLNR-003. The preset pattern method is as follows: A photomask with the preset pattern is placed on the substrate, exposed to ultraviolet light for 10-20 seconds, and the exposed area photoresist is removed by development, thereby realizing pattern transfer.
[0016] In S2, the magnetron sputtering power is 100-200W and the deposition rate is 0.05-0.2nm / s; if thermal evaporation is used, the evaporation current is controlled at 80-160A.
[0017] In S3, the carbon source gas is CH4, the gas flow rate is 10~30 sccm, the growth temperature of chemical vapor deposition is 800~1000℃, and the growth time is 5~15 min.
[0018] In S4, the metal deposition method is magnetron sputtering or evaporation coating. After the metal deposition is completed, the device will be immersed in acetone solution again for stripping to remove the photoresist and excess metal on its surface. The large metal electrode area has outwardly extending leads that overlap with the graphene electrode area.
[0019] In S5, the two-dimensional material is graphene or MoS2; the annealing temperature is 250~300℃, and the annealing time is 30~60min.
[0020] Compared with the prior art, the beneficial effects of the present invention are: 1. The present invention first provides a van der Waals contact electrode, which does not require the two-dimensional material region to be tested to directly undergo metal deposition or contact with metal, thereby effectively reducing interface damage, defects and contamination. This structure can improve the fabrication consistency and stability of the device.
[0021] 2. Furthermore, in order to achieve patterned deposition of the graphene layer, this application also envisions using a Cu catalyst layer to grow graphene, followed by thermal evaporation to remove the Cu, leaving only graphene as a van der Waals contact electrode in the two-dimensional material channel contact region. The graphene layer can improve carrier injection, reduce the effects of Fermi level pinning and Schottky barrier, and lower contact resistance. Attached Figure Description
[0022] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0023] Figure 1 A flowchart of the preparation process provided in the embodiments of the present invention; Figure 2 A top view of the device structure provided in an embodiment of the present invention; Figure 3 For Example 1 and Comparative Example 1, I D -V D Output characteristic curve; in, Figure 3 In (a), I is the contact electrode described in Example 1. D -V D Output characteristic curve, Figure 3 (b) shows the I of the contact electrode described in Comparative Example 1. D -V D Output characteristic curve. Detailed Implementation
[0024] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0025] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0026] In the context of this invention, the word "comprising" is considered to mean "particularly including". It should not be interpreted as "consisting of only".
[0027] In the description of this invention, it should be understood that the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. The symbol " / " in this document indicates that the related objects are in an "or" relationship; for example, A / B means A or B.
[0028] In the description of embodiments of the present invention, the words "exemplary" or "for example" are used to indicate that they are examples, illustrations, or descriptions. Any embodiment or design that is described as "exemplary" or "for example" in the embodiments of the present invention should not be construed as being more preferred or advantageous than other embodiments or design. Specifically, the use of the words "exemplary" or "for example" is intended to present the relevant concepts in a specific manner.
[0029] In the description of the embodiments of the present invention, unless otherwise stated, "a plurality of" means two or more.
[0030] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments and comparative examples.
[0031] Example 1 This embodiment provides a method for preparing a graphene van der Waals contact electrode based on a sacrificial copper catalyst layer, specifically including the following steps: S1. Substrate cleaning and photolithography patterning A SiO2 / Si substrate was selected as the device substrate, with a SiO2 layer thickness of 300 nm and a heavily doped Si substrate serving as the global back gate. The substrate was ultrasonically cleaned sequentially with acetone, deionized water, and isopropanol, with each cleaning agent lasting 10 minutes. It was then dried with nitrogen and subjected to heat drying to remove residual impurities from the substrate surface.
[0032] After substrate cleaning, AZ5214E photoresist was spin-coated onto the substrate surface. The photoresist was dropped onto the SiO2 / Si substrate surface and spin-coated at 3500 rpm for 45 s, followed by pre-baking at 100℃ for 120 s. After drying, a photomask with a pre-defined graphene electrode pattern was aligned with the substrate, and pattern transfer was performed using UV exposure. The exposure time was 12 s. After exposure, the sample was developed in a developer for 45 s to remove the photoresist in the exposed areas, thus forming blank areas on the substrate surface corresponding to the pre-defined graphene electrode pattern. The spacing between the coaxial electrodes was 20 μm, resulting in a patterned substrate for subsequent construction of contact areas in two-dimensional semiconductor devices.
[0033] Deposition and stripping of S2.Cu sacrificial catalyst layer A Cu metal layer with a thickness of 200 nm is deposited on the surface of a patterned substrate. The metal deposition process is performed using magnetron sputtering.
[0034] After metal deposition, the device is immersed in acetone solution to strip the photoresist, removing the photoresist and excess metal layer on its surface, and finally forming a Cu sacrificial catalyst layer on the substrate surface.
[0035] S3. Graphene growth and thermal evaporation removal of Cu layer The Cu sacrificial catalyst layer sample was placed in a chemical vapor deposition apparatus, CH4 was introduced at a flow rate of 18 sccm, the growth temperature was raised to 1000℃, and the growth time was set to 5 min, so that a continuous monolayer or few-layer graphene film with a thickness of 0.8 nm was formed on the surface of the Cu layer.
[0036] After the graphene film is formed, the CH4 flow is stopped, and annealing is continued under an Ar / H2 protective atmosphere at a temperature of 1080℃ for 40 minutes. This allows the Cu sacrificial catalyst layer to be removed by thermal evaporation or volatilization. After removal, only the graphene layer remains in the patterned region, thus obtaining the graphene layer contact electrode.
[0037] S4.Cr / Au metal large electrode deposition and stripping A new photomask is introduced onto the aforementioned graphene layer contact electrode for a second photolithography process, and the area of the second photolithography should partially overlap with the graphene film obtained in S3, such as... Figure 2 As shown, the second photolithographic region is distributed around the graphene electrode region. The photolithography method is the same as in S1, resulting in a secondary pre-defined pattern region. A Cr layer and an Au layer are sequentially deposited in the secondary pre-defined pattern region, with the Cr layer having a thickness of 5 nm and the Au layer a thickness of 50 nm.
[0038] After the Cr / Au metal deposition is completed, the device is immersed in an acetone solution again for stripping to remove the photoresist and excess metal layer on its surface, ultimately forming a large Cr / Au metal electrode that partially overlaps with the graphene electrode. The Cr / Au metal leads are used for external electrical connections.
[0039] S5. Transfer and annealing of the two-dimensional material to be tested like Figure 1 As shown, a 1 nm thick MoS2 layer was transferred to the two-dimensional material region of the sample obtained in S4 using a dry transfer method, covering and fully contacting the graphene electrode region to form a van der Waals contact, but not contacting the Cr / Au metal lead-out end.
[0040] After the transfer is completed, the device is annealed to reduce residual organic matter and interfacial adsorbed impurities during the transfer process. The annealing temperature is 300℃ and the annealing time is 60 min.
[0041] Example 2 This embodiment provides another method for preparing a graphene van der Waals contact electrode based on a sacrificial copper catalyst layer, which specifically includes the following steps: S1. Substrate cleaning and photolithography patterning SiO2 / Si was selected as the device substrate, with the SiO2 layer having a thickness of 100 nm, and the heavily doped Si substrate serving as the global back gate. The substrate was ultrasonically cleaned sequentially with acetone, isopropanol, and deionized water, with each cleaning agent lasting 10 minutes. It was then dried with nitrogen and subjected to heat drying to remove residual impurities from the substrate surface.
[0042] After substrate cleaning, AZ5214E photoresist was spin-coated onto the substrate surface. The photoresist was dropped onto the SiO2 / Si substrate surface and spin-coated at 3000 rpm for 60 seconds, followed by pre-baking on a 90℃ heating stage for 120 seconds. After drying, a photomask with a pre-defined graphene electrode pattern was aligned with the substrate, and pattern transfer was performed using UV exposure. The exposure time was 10 seconds, followed by development in a developer for 40 seconds to remove the photoresist from the exposed areas, thus forming blank areas on the substrate surface corresponding to the pre-defined graphene electrode pattern. The spacing between the coaxial electrodes was 20 μm, which will be used for the subsequent construction of contact areas for two-dimensional semiconductor devices.
[0043] Deposition and stripping of S2.Cu sacrificial catalyst layer A Cu metal layer with a thickness of 50 nm is deposited on the substrate surface after photolithography patterning. The metal deposition process is performed using magnetron sputtering.
[0044] After the metal deposition is completed, the sample is immersed in an acetone solution to strip the photoresist, thereby removing the photoresist and excess metal layer on its surface, and finally forming a Cu sacrificial catalyst layer on the substrate surface.
[0045] S3. Graphene growth and thermal evaporation removal of Cu layer The Cu sacrificial catalyst layer was placed in a chemical vapor deposition apparatus, CH4 was introduced at a flow rate of 18 sccm, the growth temperature was raised to 800℃, and the growth time was set to 15 min, so that a continuous monolayer or few-layer graphene film with a thickness of 0.34 nm was formed on the surface of the Cu layer.
[0046] After the graphene film is formed, the CH4 supply is stopped, and annealing is continued under an Ar / H2 protective atmosphere at a temperature of 1080℃ for 40 minutes, allowing the Cu sacrificial catalyst layer to be thermally evaporated or volatilized and removed. After removal, only the graphene layer remains in the patterned area, thus obtaining the graphene layer contact electrode.
[0047] S4.Cr / Au Metallic Large Electrode Deposition and Stripping A new photomask is introduced onto the aforementioned graphene layer contact electrode for a second photolithography process, and the area lithographically applied in the second photolithography should partially overlap with the graphene electrode obtained in S3. The photolithography method is the same as in S1, resulting in a secondary pre-defined pattern area. A Cr layer and an Au layer are sequentially deposited in the secondary pre-defined pattern area, with the Cr layer having a thickness of 3 nm and the Au layer having a thickness of 30 nm.
[0048] After Cr / Au metal deposition, the sample is immersed in an acetone solution for stripping to remove the photoresist and excess metal layer, ultimately forming Cr / Au metal leads that partially overlap with the graphene layer. These Cr / Au metal leads are used for external electrical connections.
[0049] S5. Transfer and annealing of the two-dimensional material to be tested A 1 nm thick layer of MoS2 was transferred to the two-dimensional material region of the sample obtained in S4 using a dry transfer method, ensuring that the MoS2 covered and fully contacted the graphene electrode, but did not contact the Cr / Au metal large electrode. After the transfer, the device was annealed to reduce residual organic matter and interfacial adsorbed impurities from the transfer process. The annealing temperature was 300 °C and the annealing time was 30 min.
[0050] Example 3 This embodiment provides another method for preparing a graphene van der Waals contact electrode based on a sacrificial copper catalyst layer, which specifically includes the following steps: S1. Substrate cleaning and photolithography patterning SiO2 / Si was selected as the device substrate, with the SiO2 layer having a thickness of 150 nm, and the heavily doped Si substrate serving as the global back gate. The substrate was ultrasonically cleaned sequentially with acetone, isopropanol, and deionized water, with each cleaning agent lasting 15 minutes. It was then dried with nitrogen and subjected to heat drying to remove residual impurities from the substrate surface.
[0051] After substrate cleaning, AZ5214E photoresist was spin-coated onto the substrate surface. The photoresist was dropped onto the SiO2 / Si substrate surface and spin-coated at 4000 rpm for 30 s, followed by pre-baking at 100℃ for 60 s. After drying, a photomask with a pre-defined graphene electrode pattern was aligned with the substrate, and pattern transfer was performed using UV exposure. The exposure time was 20 s, followed by development in a developer for 60 s to remove the photoresist from the exposed areas, thus forming blank areas on the substrate surface corresponding to the pre-defined graphene electrode pattern. The spacing between the coaxial electrodes was 20 μm, which will be used for the subsequent construction of contact areas for two-dimensional semiconductor devices.
[0052] Deposition and stripping of S2.Cu sacrificial catalyst layer A Cu metal layer with a thickness of 500 nm is deposited on the substrate surface after photolithography patterning. The metal deposition process is performed using magnetron sputtering.
[0053] After the metal deposition is completed, the sample is immersed in an acetone solution to strip the photoresist, thereby removing the photoresist and its excess metal layer. Finally, a Cu sacrificial catalyst layer is formed on the substrate surface, which is referred to as the Cu sacrificial catalyst layer electrode.
[0054] S3. Graphene growth and thermal evaporation removal of Cu layer The Cu sacrificial catalyst electrode was placed in a chemical vapor deposition apparatus, CH4 was introduced at a flow rate of 18 sccm, the growth temperature was raised to 800℃, and the growth time was set to 15 min, so that a continuous monolayer or few-layer graphene film with a thickness of 1 nm was formed on the surface of the Cu layer.
[0055] After the graphene film is formed, the CH4 supply is stopped, and annealing is continued under an Ar / H2 protective atmosphere at a temperature of 1080℃ for 40 minutes, allowing the Cu sacrificial catalyst layer to be thermally evaporated or volatilized and removed. After removal, only the graphene layer remains in the patterned area, thus obtaining the graphene layer contact electrode.
[0056] S4.Cr / Au Metallic Large Electrode Deposition and Stripping A new photomask is introduced onto the aforementioned graphene layer contact electrode for a second photolithography process, and the area lithographically applied in the second photolithography should partially overlap with the graphene film obtained in S3. The photolithography method is the same as in S1, resulting in a secondary pre-defined pattern area. A Cr layer and an Au layer are sequentially deposited in the secondary pre-defined pattern area, with the Cr layer having a thickness of 10 nm and the Au layer having a thickness of 100 nm.
[0057] After Cr / Au metal deposition, the sample is immersed in an acetone solution for stripping to remove the photoresist and excess metal layer, ultimately forming Cr / Au metal leads that partially overlap with the graphene layer. These Cr / Au metal leads are used for external electrical connections.
[0058] S5. Transfer and annealing of the two-dimensional material to be tested A 1 nm thick layer of MoS2 was transferred to the graphene electrode region obtained in S4 using a dry transfer method. This ensured that the MoS2 covered and fully contacted the graphene electrode but did not contact the Cr / Au metal large electrode. After transfer, the device was annealed at 250 °C for 60 min to reduce residual organic matter and interfacial adsorbed impurities.
[0059] Comparative Example 1 This comparative example provides a method for preparing a metal / MoS2 direct contact electrode without introducing a graphene van der Waals contact layer, for comparison with Example 1.
[0060] S1. Transfer of monolayer MoS2 and patterning of source and drain electrodes A SiO2 / Si substrate was selected as the device substrate, and a monolayer of MoS2 was transferred onto the surface of the SiO2 / Si substrate. Subsequently, photoresist was spin-coated onto the MoS2 surface, and the source and drain electrode patterns were defined through exposure and development processes.
[0061] S2. Deposition and stripping of metal source and drain electrodes After patterning, metal source / drain electrodes are directly deposited on the MoS2 surface using thermal evaporation, electron beam evaporation, or magnetron sputtering. These metal source / drain electrodes are Cr / Au electrodes. After metal deposition, the sample is subjected to acetone for stripping to remove the photoresist and excess metal layer, ultimately forming a direct metal / MoS2 contact structure. Following the fabrication of the metal source / drain electrodes, the device is annealed at 300°C for 30 minutes.
[0062] Electrical performance tests were performed on the devices obtained in Example 1 and the comparative example above: The MoS2 device prepared in Example 1 was placed on a probe stage for electrical performance testing, with the test probes contacting the Cr / Au metal leads. A drain-source voltage V was applied across the device at gate voltages of 0 V, 10 V, and 20 V. D And perform a scan, while simultaneously measuring the corresponding drain current I. D To obtain the device's I D -V D Output characteristic curves were generated, and the electrical contact performance between the graphene van der Waals contact electrode and MoS2 was characterized based on the test results. The test results are as follows: Figure 1 As shown in (a), the drain current of the device reaches 10. 7 The A-level magnitude indicates that an effective electrical contact has been formed between the graphene electrode and MoS2.
[0063] The MoS2 device prepared in Comparative Example 1 was placed on a probe stage for electrical performance testing, with the test probes contacting the metal source and drain electrodes respectively. A drain-source voltage V was applied across the device at gate voltages of 0 V, 10 V, and 20 V. D And perform a scan, while simultaneously measuring the corresponding drain current I. D To obtain the device's I D V D Output characteristic curves were generated, and the electrical contact performance between the metal electrode and MoS2 was characterized based on the test results. Test results are as follows: Figure 3 As shown in Figure (b), under the same test conditions, the drain current of the comparative device is significantly lower than that of Example 1.
[0064] The difference between this comparative example and Example 1 is as follows: In Example 1, a graphene film is first grown in situ on the surface of a pre-fabricated Cu electrode, then the Cu sacrificial layer is removed, leaving the graphene on the substrate surface as a contact electrode. A monolayer of MoS2 is then transferred to the surface of the graphene electrode, forming a MoS2 / graphene van der Waals contact structure, while the metal electrode is deposited at a distance to achieve electrical connection. In contrast, this comparative example does not introduce a graphene film; the metal electrode is directly deposited on the MoS2 surface, forming a direct metal / MoS2 contact structure. Under the same testing conditions, the drain current of the device prepared in Example 1 is significantly higher than that in Comparative Example 1, indicating that using graphene as the van der Waals contact layer between MoS2 and the metal electrode is beneficial for improving the electrical contact performance between the electrode and MoS2.
Claims
1. A graphene van der Waals contact electrode based on a sacrificial copper catalyst layer, characterized in that, The contact electrode uses a SiO2 / Si substrate or a SiO2 / SiC as the device substrate, wherein Si or conductive SiC is used as the global back gate. The contact electrode has three regions on its SiO2 layer: the two-dimensional material to be tested region, the graphene electrode, and the large metal electrode, which are sequentially overlapped. The two-dimensional material to be tested region is used to place the material to be tested and is in contact with the graphene electrode. The large metal electrode partially covers the graphene layer electrode, and the two-dimensional material to be tested and the large metal electrode are not in direct contact. The large metal electrode region includes at least one metal element.
2. The graphene van der Waals contact electrode based on a sacrificial copper catalyst layer as described in claim 1, characterized in that, The two-dimensional material region under test only contacts the graphene electrode and not the large metal electrode. The large metal electrode at the far end serves as a lead-out terminal and is electrolytically connected to the graphene electrode for connecting to the external test circuit.
3. The graphene van der Waals contact electrode based on a sacrificial copper catalyst layer as described in claim 1, characterized in that, The contact electrode first constructs a Cu layer in the graphene electrode region by magnetron sputtering or evaporation deposition. The Cu layer serves only as a catalyst layer for graphene growth. After graphene is formed on the surface of the Cu layer, the Cu layer is removed by thermal evaporation, so that only graphene remains in the predetermined graphene electrode region as the graphene electrode.
4. The graphene van der Waals contact electrode based on a sacrificial copper catalyst layer as described in claim 3, characterized in that, In the contact electrode substrate, the SiO2 layer has a thickness of 100-300 nm; in addition, the Si substrate or SiC substrate serving as the global back gate is of the conductive doped type. The thickness of the graphene layer is 0.34-1 nm; Alternatively, the two-dimensional material region to be tested may be covered with graphene material or MoS2 with a thickness of 0.34-1 nm, and the two-dimensional material to be tested may be placed on it. Alternatively, the large metal electrode includes a Cr layer and an Au layer, wherein the Cr layer is close to the SiO2 surface and has a thickness of 3-10 nm, and the Au layer completely covers the Cr layer and has a thickness of 30-100 nm.
5. The method for preparing the graphene van der Waals contact electrode based on a sacrificial copper catalyst layer according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Substrate cleaning and photolithography patterning SiO2 / Si or SiO2 / SiC substrates are selected as the device substrates, and Si or conductive SiC is used as the global back gate. The substrates are cleaned and dried. A preset electrode pattern is formed on the SiO2 surface by photolithography to obtain a preset pattern substrate. Deposition and stripping of S2.Cu sacrificial catalyst layer On the surface of the pre-patterned substrate obtained in S1, a Cu sacrificial catalyst layer is formed by magnetron sputtering or evaporation to obtain a Cu sacrificial catalyst layer electrode. S3. Graphene growth and thermal evaporation removal of Cu layer The Cu sacrificial catalyst electrode obtained in S2 is placed in a chemical vapor deposition apparatus. A carbon source gas is introduced to grow a single or few-layer graphene film on the surface of the Cu sacrificial catalyst. After the carbon source is stopped, annealing is performed in a reducing gas atmosphere to remove the Cu sacrificial catalyst by thermal evaporation or volatilization, leaving only the graphene layer, which is referred to as the graphene layer contact electrode. S4. Deposition and stripping of metal leads A second photolithography is performed on the graphene layer contact electrode to form a second preset pattern area. Metal is deposited in the second preset pattern area to form a large metal electrode that does not overlap with the graphene layer and only partially overlaps it. S5. Transfer and annealing of the two-dimensional material to be tested The two-dimensional material is partially covered on the surface of the graphene film to form the two-dimensional material region to be tested, which is then in contact with the graphene electrode; annealing completes the process.
6. The preparation method according to claim 5, characterized in that, In S1, the cleaning includes cleaning with organic reagents and water or cleaning using the RCA standard wet cleaning method; Furthermore, the substrate was ultrasonically cleaned sequentially with acetone, isopropanol, and deionized water, with each cleaning agent taking 8-15 minutes.
7. The preparation method according to claim 5, characterized in that, The photolithography method described in S1 and S4 is as follows: spin-coating photoresist on the substrate surface and forming a preset electrode pattern through exposure and development processes. The feasible photoresist models are one of AZ5218E, AZ5206E, AZ5200NJ, AZ nLoF 5510, and AZ LNR-003. The preset pattern method is as follows: place the photomask of the preset pattern on the substrate, expose it under ultraviolet light for 10-20 seconds, remove the photoresist in the exposed area, thereby realizing pattern transfer.
8. The preparation method according to claim 5, characterized in that, In S2, the magnetron sputtering adopts a DC sputtering mode with a power of 100-200W and a deposition rate of 0.05-0.2nm / s; if thermal evaporation is used, the evaporation current is controlled at 80-160A. In S3, the carbon source gas is CH4, the gas flow rate is 10~30 sccm, the growth temperature of chemical vapor deposition is 800~1000℃, and the growth time is 5~15 min.
9. The preparation method according to claim 5, characterized in that, In S4, the metal deposition method is magnetron sputtering or evaporation coating. After the metal deposition is completed, the device will be immersed in acetone solution again for stripping to remove the photoresist and excess metal on its surface. The metal region has outwardly extending leads that overlap with the graphene layer.
10. The preparation method according to claim 5, characterized in that, In S5, the two-dimensional material is graphene or MoS2; the annealing temperature is 250~300℃, and the annealing time is 30~60min.